2016
DOI: 10.3390/wevj8040818
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Causes of PEV Success Across U.S. Metro Areas

Abstract: Short AbstractUsing 2014 U.S. light duty PEV registrations by make and model, this paper assesses the causes of Plug-in Electric Vehicle (PEV) success across U.S. states focusing on areas that had incentive and utility programs supporting PEV adoption. Market segments investigated were (1) luxury/performance (>$60,000 list price), (2) mid-market ($40-50,000), (3) mass market (<$40.000), and (4) total. States with either exclusive or preferential BEV incentives are a focus. BEV-biased incentives proved to be ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…(3) Is a standard method of range extension for intercity travel likely to emerge from the multiple competing technological options? (4) What infrastructure incentives to support PEV sales are the best options for possible U.S. state supplements of the reviewed policies?…”
Section: Broad Questions About Which Technology Innovation Paths To Pmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) Is a standard method of range extension for intercity travel likely to emerge from the multiple competing technological options? (4) What infrastructure incentives to support PEV sales are the best options for possible U.S. state supplements of the reviewed policies?…”
Section: Broad Questions About Which Technology Innovation Paths To Pmentioning
confidence: 99%
“…In companion papers [3,4] we have addressed 2014 U.S. consumer behavior patterns without looking at lessons from Canada and Europe. When we divided the plug-in vehicles available into three market segments based on price (Tables 1-3), it was observed that the PHEV obtained largest shares of total available plug-in vehicles (PEVs) in the low price segment, while the BEV captured the largest share in the high price luxury/performance segment.…”
Section: A Summary Of Us Findingsmentioning
confidence: 99%
See 1 more Smart Citation